Religious Assistance and Economic Strengthening Through Empowering Boboko Craftsman - Yandi Heryandi; Indah Nursuprianah (MASI Mandiri Edukasi, 2025)
This service is expected to create synergy between spiritual and material aspects. Religious assistance and economic strengthening aim to strengthen religion while improving the economic welfare of Boboko craftsmen. The method used is Service Learning, as the application of lecture knowledge to provide meaningful benefits to society. The participatory and collaborative approach includes the Investigation and Problem Mapping stages, training and assistance for economic strengthening, religious assistance, and monitoring and evaluation. The results show the effectiveness of the religious assistance program for boboko craftsmen in the Pagar Gunung Block, especially children and teenagers. The existence of the younger generation living in the Pagar Gunung Block is a hope for the sustainability of this religious program. Boboko craftsmen can increase innovation in boboko craft products and empower the local economy. There is a need for an innovation strategy to increase the empowerment of boboko craftsmen in the Pagar Gunung Block by improving the quality and competitiveness of their products. Boboko products began to be marketed through social media and local shops, directly increasing craftsmen's income.